Conformational switch of harmonin, a submembrane scaffold protein of the hair cell mechanoelectrical transduction machinery. Issue 15 (10th July 2017) - Bahloul, Amel; Pepermans, Elise; Raynal, Bertrand; Wolff, Nicolas; Cordier, Florence; England, Patrick; Nouaille, Sylvie; Baron, Bruno; El‐Amraoui, Aziz; Hardelin, Jean‐Pierre; Durand, Dominique; Petit, Christine
Abstract : Mutations in the gene encoding harmonin, a multi‐PDZ domain‐containing submembrane protein, cause Usher syndrome type 1 (congenital deafness and balance disorder, and early‐onset sight loss). The structure of the protein and biological activities of its three different classes of splice isoforms (a, b, and c) remain poorly understood. Combining biochemical and biophysical analyses, we show that harmonin‐a1 can switch between open and closed conformations through intramolecular binding of its C‐terminal PDZ‐binding motif to its N‐terminal supramodule NTD‐PDZ1 and through a flexible PDZ2‐PDZ3 linker. This conformational switch presumably extends to most harmonin isoforms, and it is expected to have an impact on the interaction with some binding partners, as shown here for cadherin‐related 23, another component of the hair cell mechanoelectrical transduction machinery. Abstract :